Proteksi Katodik pada Elektrode Zn Metode Sacrificial Anode untuk Peningkatan Kinerja Sistem Akumulator Air Laut - Sri Wahyu Suciyati; Gurum Ahmad Pauzi; Junaidi Junaidi; L Kamalia (Jurnal Teori dan Aplikasi Fisika, 2020)
Corrosion to the Zn electrode in the seawater accumulator system can be controlled by the cathodic protection of the sacrificial anode system. The mechanism is via anode sacrifice such as Al which has a negative potential connected to the Zn structure to provide extra electrons. The Zn electrode design is protected by an Al offering anode to form Cu-ZnAl electrode pairs arranged in series to form a seawater accumulator. Testing of electrodes with sacrificial anode system cathodic protection (Cu-ZnAl) compared to unprotected electrodes (Cu-Zn) for 48 hours showed no-load voltages of 10.19 V (Cu-Zn) and 12.89 V while the power generated was 48.36 mW and 49.37 mW. The average power after 3 watt LED loading was obtained 12.03 mW (day 1) and 12.56 mW (day 2) for the Cu-ZnAl electrode, while the Cu-Zn electrode obtained an average power of 6, 68 mW (day 1) and 10.09 mW (day 2). The corrosion rates after two days of using the Cu-Zn and Cu-ZnAl electrode pairs were obtained 0.008136 mm/year (Zn) and 0.0749626 mm/year (ZnAl).